Drug Marketing in Tropical Regions and Its Effect on Pharmacovigilance Awareness and Reporting - Suraj Sen; Anit Jha; Rajeev Ratan; Aman; Ashish Pal (International Journal of Tropical Medicines, 2026)
Drug marketing practices in tropical regions present a complex interplay between pharmaceutical promotion, healthcare infrastructure limitations, and public health outcomes. These regions – characterized by high disease burden, socio-economic disparities, and diverse healthcare delivery systems – often experience unique challenges in ensuring safe and rational drug use. Aggressive and sometimes unregulated marketing strategies by pharmaceutical companies may significantly influence prescribing behavior, patient compliance, and, ultimately, pharmacovigilance systems. Pharmacovigilance, defined as the science and activities related to the detection, assessment, understanding, and prevention of adverse drug reactions (ADRs), is crucial for ensuring drug safety post-marketing. However, in tropical regions, pharmacovigilance awareness and reporting remain suboptimal due to factors such as inadequate training, poor regulatory enforcement, lack of infrastructure, and limited public awareness. This review critically examines the influence of drug marketing strategies on pharmacovigilance awareness and ADR reporting in tropical regions. It explores marketing techniques employed, their impact on healthcare professionals and patients, and the systemic barriers that hinder effective pharmacovigilance practices. Additionally, it highlights the need for ethical marketing, regulatory strengthening, and capacity building to enhance drug safety monitoring. The article aims to provide a structured understanding of how marketing practices shape pharmacovigilance outcomes and suggests strategies to bridge gaps in awareness and reporting systems in tropical healthcare settings.
Keywords: ADR reporting; Adverse drug reactions; Drug marketing; Healthcare systems; drug safety; pharmaceutical promotion; pharmacovigilance; public health; regulatory affairs; tropical regions